2009
DOI: 10.7202/037874ar
|View full text |Cite
|
Sign up to set email alerts
|

L’impact du suicide d’un patient chez des professionnels en santé mentale

Abstract: Résumé Cet article rapporte les résultats d’une recherche réalisée auprès de 141 professionnels en santé mentale pratiquant au Québec et ayant vécu le suicide d’un patient. Les professionnels ont réagi à cet événement différemment en fonction de leur sexe. Les femmes y ont répondu par un niveau de stress élevé au cours du premier mois, alors que les hommes ont dévoilé un niveau de stress faible. Le niveau élevé de stress relevé chez les femmes était accompagné de répercussions initialement plus inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 74 publications
(81 reference statements)
2
12
0
Order By: Relevance
“…Subgroup variations in the total score of the IES-R are in part related to the predictors of stress reactions after a patient suicide and to the profession [ 6 , 9 , 10 ]. Mean scores of the IES-R were higher for emotional closeness to the patient (M = 15.8; no closeness M = 10.3), insufficient support received (M = 17.6; sufficient support M = 11.6) and nurses (M = 14.4) as well as educators (M = 14.1; psychiatrists M = 12.0, social workers M = 11.3, psychologists M = 10.7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subgroup variations in the total score of the IES-R are in part related to the predictors of stress reactions after a patient suicide and to the profession [ 6 , 9 , 10 ]. Mean scores of the IES-R were higher for emotional closeness to the patient (M = 15.8; no closeness M = 10.3), insufficient support received (M = 17.6; sufficient support M = 11.6) and nurses (M = 14.4) as well as educators (M = 14.1; psychiatrists M = 12.0, social workers M = 11.3, psychologists M = 10.7).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have investigated predictors of severity for stress reactions, however findings pertaining to patients or professionals' characteristics have been inconsistent [ 6 ]. The length and intensity of the relationship with the patient proved to be significant, i.e., professionals who felt closer to, or were in a therapeutic relationship with the patient for longer reported higher levels of stress [ 6 , 9 , 10 ]. Support was identified as a protective factor [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been seen that the suicide of a patient generates changes in health care workers both at their work and personal life. Significant among psychiatrists are feelings of professional failure, questions about their expertise, concerns about legal repercussions and changes in their professional practice (Campbell & Fahy, 2002;Grad & Michel, 2005;Grad, Zavasnik & Groleger, 1997;Hendin, Lipschitz, Maltsberger, Haas & Wynecoop, 2000;Henry, Séguin & Drouin, 2008;Horn, 1994). However, it has been shown that to the extent that physicians acquire greater professional experience, the guilt, low self-esteem and social withdrawal experienced after the suicide of a patient decreases (Chemtob et al, 1988).…”
Section: Introductionmentioning
confidence: 99%